Fluxos migratórios e visibilidade feminina em Chimamanda Adichie e Zadie Smith - Valença, Letícia Ritter de Abreu (2022)
Regarding the process of identity search experienced by the contemporary and globalized subject, marginalized women suffer intersectional oppressions, in an attempt to socialize. Therefore, aspects of identity and cultural belonging emerge in the works of migrant writers, such as Chimamanda Adichie and Zadie Smith. In their respective and renowned novels Americanah (2013) and White Teeth (2001), it is possible to capture elements of colonized national roots, which are intertwined by the hegemonic cultural domain of the United States, in the case of the former, and of England, in the case of the latter. In this intersection, there is the figuration of the black and immigrant woman, represented by Ifemelu, in Adichie's novel and by Irie, in Smith's. From the understanding of the cosmovision resulting from the figuration of black and immigrant women in contexts of identity negotiation, it is possible to perceive the discontinuation of hegemonic values. Therefore, through the comparative methodology, the objective of the present study is to analyze the feminine visibility and the social contexts in which the protagonists of these narratives are inserted, identifying similarities and differences in the main thematic axes that approach the racial, cultural, and gender dimensions represented in the novels. The analysis, which is divided into three main thematic axes, is subdivided into three central moments, of submission, questioning and, finally, subversion to the hegemonic norm that guarantees racial, cultural, and gender hierarchies. In order to comprehend the exchange between literature and society, it is pertinent to use concepts such as identity in the Postmodern period, by Stuart Hall (2006), the fragmentation of the modern tradition, by Antoine Compagnon (1996), the discontinuation of the “master narratives”, by Jean-François Lyotard (2009), and the consequent weakening of hegemonic values, by Eduardo Coutinho (2005) and Linda Hutcheon (1991). Furthermore, to understand the point of view of the analyzed protagonists, which conceives the cultural hybridity and existence of minorities, it is possible to verify arguments such as those of Djamila Ribeiro (2017), bell hooks (1984), Chantal Lacroix (2010), and Homi Bhabha (1998). From the approximation of these novels, there are central differences, such as the generation gap the two characters have regarding the migration experience. Besides, it is possible to detect that both live moments of submission to the values determined by the racist, culturally hegemonic, and sexist norm, but they also express questions about this norm and, finally, subvert these principles. Thus, given the parallel between characters such as Irie and Ifemelu, as representative figures of black and immigrant women today, it is noticeable that these representations can contribute intensely to the social revaluation made by the reader when concluding the mimetic circle. The construction of characters such as these, who use the context of systemic racism, classism, and sexism to then subvert them into their own figurations, fragment a conservative tradition of a behavioral ideal of black and immigrant women and enable the acceptance of otherness.